TINJAUAN YURIDIS TERHADAP ASEAN-CHINA FREE TRADE AGREEMENT (ACFTA) DAN IMPLIKASINYA TERHADAP PENGATURAN PENANAMAN MODAL - SUSPIM GP NAINGGOLAN; BUDIMAN GINTING; MAHMUL SIREGAR (TRANSPARENCY, 2013)
ASEAN-China Free Trade Agreement (ACFTA) is a free agreement which is formed the member countries of ASEAN with China. ACFTA is one of the free Trade Agreement that has been agreed since 2001, and are formed based on the basic of international law, namely the Framework Agreement and Comprehensive Economic Co-operation between ASEAN and The People’s Republic of China, which is signed on 4 November 2002 in Phnom Penh, Cambodia, by the heads of government from ASEAN countries and The People’s of Republic of China. Indonesia is a big Country and also one of pioneers of the establishment of ASEAN region which also supports the establishment of ASEAN-China Free Trade Agreement. That is why Indonesia must implication to regulate in Investment Law. The Investment Of law was being hope to Increase The economic Of Indonesia form using that Agreement and to cope with  negatife consequence in ASEAN –China Free Trade Agreement Keywords: ACFTA, Free Trade, Free Trade Agreement